Work outcome in persons with musculoskeletal diseases: comparison with other chronic diseases & the role of musculoskeletal diseases in multimorbidity. Issue 1 (December 2017) - van der Zee-Neuen, Antje; Putrik, Polina; Ramiro, Sofia; Keszei, Andras; de Bie, Rob; Chorus, Astrid; Boonen, Annelies
Abstract Background Chronic diseases and multimorbidity are increasingly common among persons in working age. This study explores the impact of type, number and combinations of chronic diseases with focus on the role of MSKD on (1) adverse work status (i.e. work disability (WD), economic unemployment (UE) or receiving a living allowance (LA)) and on (2) the occurrence of sick leave. Methods Subjects participating in a Dutch household survey, who were ≤65 years and could have paid work, provided data on socio-demographics and nine physician diagnosed chronic diseases. To explore the independent association of each chronic disease, of multimorbidity and of MSKD in context of multimorbidity with 1) work status (employed, WD, LA, UE) and 2) sick leave (SL) in those employed, multinomial logistic regressions and logistic regressions were used, respectively. Results Among 5396 subjects, MSKD was the most common morbidity (17%), multimorbidity occurred in 755/5396 (14%), 436/755 (61%) of subjects with multimorbidity had an MSKD. For MSKD the odds of WD, LA and UE were 2.06 [95% CI 1.56;2.71], 2.15[1.18;3.91] and 1.35[0.94;1.96], respectively, compared to being employed and the odds of SL in MSKD were 2.29[1.92;2.73]. Mental diseases had a stronger impact on all these outcomes. The odds for adverse work outcomes increased strongly with an increasing number of diseases. When an MSKD was part of multimorbidity, an additional impact on the association with WD and SL was observed. Conclusions Multimorbidity has a stronger impact on all work outcomes compared to single chronic diseases. The presence of the MSKD in the context of multimorbidity amplifies the chance of WD or SL.